Marka idealnej partii politycznej w opinii wyborców o różnych preferencjach ideologicznych i partyjnych - Turska-Kawa, Agnieszka (Political Preferences, 2013)
The present article presents results of research conducted with the working assumption that voters perceive political parties in terms of traits characteristics for people, giving them a unique identity. Research was focused on defining the „personality" of a perfect political party; voters were asked about desired intensity of certain characteristics in such imagined perfect political entity. The taxonomy of traits presented to the respondents used the HEXACO model, by Kibeom Lee and Michael C. Aschton, which refers to a six-dimensional personality structure. The authors distinguished the following personality factors in the model: Honesty, Emotionality, Extraversion, Agreeableness, Conscientiousness and Openness to Experience.